Stepwise Luweero library of GAP: chemical control of BCTB - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Chemical control of BCTB, Clip of a practice that make up the generic set of Uganda Coffee recommended good agricultural practices, in addition to the additional recommended climate smart agricultural practices